Nation shapes : the story behind the world's borders - Shelley, Fred M., 1952- (Gale virtual reference library, 2013)
This book examines the importance of country boundaries, the disconnects between these borders, related factors such as cultures, religions, and economies, and how conflicts over boundaries between neighboring countries are articulated.